Atypical Case of Three Dental Implants Displaced into the Maxillary Sinus - João Felipe Bonatto Bruniera; Yara Teresinha Corrêa Silva-Sousa; Paulo Esteves Pinto Faria (Hindawi Limited, 2015)
Oral rehabilitation with dental implants has become a routine treatment in contemporary dentistry. The displacement of dental implants into the sinus membrane, a complication related to the maxillary sinus, is one of the most common accidents reported in the literature. The treatment for this complication is the surgical removal of the implant. A 60-year-old woman with three dental implants displaced into the maxillary sinus (one implant displaced into the left maxillary sinus and two implants displaced into the right maxillary sinus) underwent surgery for removal of the implants. The surgery to remove the implants was performed under local anesthesia through the Caldwell-Luc technique. The patient was subsequently administered antibiotic, anti-inflammatory, and analgesic drugs. The patient returned 7 days after the surgery for suture removal and is being regularly monitored to determine whether future rehabilitation of the edentulous area is necessary. In conclusion, surgical removal of the dental implant displaced into the maxillary sinus is the treatment of choice. This technique is appropriate because it allows the use of local anesthesia and provides direct visualization for the removal of the implants.